How far is too far?: Investigating purchasing across packaged goods and services categories for retailer branded products. (17th January 2019) - Nenycz-Thiel, Magda; Romaniuk, Jenni
Abstract : Purpose: Retailers are increasingly adding banks, gas stations, mobile services and even real estate agencies to their portfolio and branding these new ventures with the retailer name, such as Tesco Bank or Asda Money. The purpose of this paper is to test the ability of a retailer brand to stretch from traditional packaged goods categories to very different categories such as banking. Design/methodology/approach: Using data from an online survey collected from 953 UK grocery buyers, this paper examines consumers' behaviour towards UK retailer brands across four categories: soft drinks, chocolate, fuel and banking. Findings: The results show that cross-category retailer brand purchasing is stronger between categories with similar buying behaviour (e.g. soft drinks and chocolate) than in categories with very different buying behaviour (e.g. soft drinks and banking). The behavioural spill over effects are stronger for retailer brands from the same chain and persist even for unrelated categories. However, apart from fuel, the strongest cross-purchasing occurs across competing retailer-branded offers within the same category. Research limitations/implications: The main implication of this study is that behavioural spill overs for retailer brands are possible even between unrelated categories. The finding about the effects being strongest within a given chain implies that umbrella branded strategy is a key to take advantage of the effects. Practical implications: These findings extend past literature about the cross-category buying of umbrella branded store brands to very different categories. This paper highlights the challenges retailers face regarding their ability to extend the retailer brand across categories. The findings also provide insights for cross-selling retailer brands in unrelated categories to current store brand buyers. Originality/value: This is the first study to examine the use of retailer brands across a wide spectrum of categories from Soft Drinks to Fuel.